Integrasi Mandat Budaya Ke Dalam Pembelajaran Pendidikan Agama Kristen Melalui Strategi Pembelajaran Contextual Teaching And Learning - sakey, Jenet selfiani; Silalahi, Lila S; Sibarani, Mortan (Sekolah Tinggi Teologi Kadesi Bogor, 2025)
This study was motivated by the importance of improving the quality of Christian religious education (PAK) that can develop students' potential holistically through Contextual Teaching and Learning (CTL) with the aim of improving understanding of cultural mandates. The CTL learning strategy aims to integrate understanding of cultural mandates with the real-life contexts of students in order to achieve effective and meaningful learning. This study used qualitative methods, with data obtained through a literature study utilizing various sources that could answer the research objectives. The results of this study indicate that the application of CTL learning strategies can increase student engagement and understanding of cultural mandates and strengthen the relevance of PAK learning materials in everyday life. Keywords: Cultural Mandate; Contextual Teaching and Learning (CTL); Christian Religious Education